Metals in Leaves as Indicators of Atmospheric Pollution in Urban Areas - Valerio, F.; Brescianini, C.; Lastraioli, S.; Coccia, S. (International Journal of Environmental Analytical Chemistry, 1989)
Abstract The use of biological indicators to monitor atmospheric pollution is widely distributed. The analysis of heavy metals in leaves is suggested as a method for a rapid identification of polluted areas. Reproducibility and representativity of this method must be assessed. We have verified if the concentration of lead, chromium, copper, nickel and manganese in ?Quercus Ilex? leaves may be used to classify urban areas according to the level of their atmospheric pollution. Particular emphasis was placed on reproducibility of sampling and the analytical method. Preliminary results show a linear correlation between concentration of metals in atmosphere (particularly lead) and in leaves collected in the same sampling areas.
doi: 10.1080/03067318908026901doi: 10.1080/03067318908026901The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: atmospheric pollution; Heavy metals (PG); Quercus ilex leaves